Diversity on Display: Framing in the Gay Perspective Radio Program. Issue 2 (3rd July 2018) - Sugden, Ryan Charles; Terry, Christopher
Abstract : This study explores the archived content of Gay Perspective, a 1970s radio program in Milwaukee as it frames LGBTQIA+ (queer) rights in a historical context. Gay Perspective was produced by the Gay People's Union (GPU). The group was considered politically "moderate, " emphasizing educational and legal action through their engagement with radio and magazines. Gay Perspective focused much of its energy on trying to demonstrate the need for rights and attempts to demonstrate how the queer community's members could be functioning members of mainstream society. Gay Perspective is a cultural artifact that not only allows for the examination of gay identity in a different era, but also demonstrates the struggles social movements face in trying to gain access to media. The program provided a public voice to a radically underserved group, a group that was struggling with its own identity. By trying to build a community through radio, sharing resources and experiences, the program found some limited success in airing the GPU's message of tolerance. Applying the analysis through 3 frames, Cultured, Diversity, and Assimilation, this article explores how segments of the LGBTQIA+ community framed the discussion of gay rights in the 1970s and discusses how those frames have (and haven't) changed in 2018.